Estudo de aterramento da usina fotovoltaica da UFERSA - Olveira, Alysson Max Costa de (Universidade Federal Rural do Semi-Árido, 2017)
The proposed work consists in verifying the ground conditions, as well as the ground resistance values of a grid-connected photovoltaic system located in UFERSA. The system consists of 580 photovoltaic modules, distributed in 5 strings having 116 modules each, and containing individual grounding. Visual inspection of ground conditions was carried out, and with the help of a terrometer using the Wenner method, ground resistance measurements were performed, obtaining values measured above 20 Ω. These values differ from those described in standards. Therefore, it was possible to conclude that the values of earth resistance are high, if compared to the current norm in Brazil, as well as international standards, and that some constructive aspects of grounding are in disagreement with what is described in standard, and in the solar power plant project
Keywords: Usina solar; Ufersa; Aterramento; Solar power plant; Grounding; ENGENHARIAS::ENGENHARIA DE ENERGIA